2002
DOI: 10.1177/107110070202300205
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Rotation on Radiographic Evaluation of the Tibiofibular Syndesmosis

Abstract: Radiographs of 12 normal cadaveric lower extremities were prepared with each extremity in seven increments of axial rotation, ranging from 5 degrees of external rotation to 25 degrees of internal rotation. The tibiofibular clear space, the tibiofibular overlap, the width of the tibia and fibula, and the medial clear space were measured on each film. The width of the tibiofibular clear space (syndesmosis A) averaged 3.9+/-0.9 mm (range, 2 to 5.5 mm), but did not change significantly with rotation. Its size was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
107
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(112 citation statements)
references
References 8 publications
(22 reference statements)
2
107
1
2
Order By: Relevance
“…Problems related to syndesmotic reduction or fixation were further divided into four categories: malpositioning of the fibula in the tibiofibular incisure with a syndesmotic screw, tibiofibular widening (TFCS > 6 mm) (Pneumaticos et al 2002), positioning of a syndesmotic screw posterior to the posterior margin of the tibia (missed), and syndesmotic transfixation in the presence of a stable syndesmosis. A syndesmotic screw was considered unnecessary if lateral and external rotation stress tests were negative after proper reduction and fixation of the fracture at the time of reoperation (van den Bekerom 2011).…”
Section: Radiological Evaluationmentioning
confidence: 99%
“…Problems related to syndesmotic reduction or fixation were further divided into four categories: malpositioning of the fibula in the tibiofibular incisure with a syndesmotic screw, tibiofibular widening (TFCS > 6 mm) (Pneumaticos et al 2002), positioning of a syndesmotic screw posterior to the posterior margin of the tibia (missed), and syndesmotic transfixation in the presence of a stable syndesmosis. A syndesmotic screw was considered unnecessary if lateral and external rotation stress tests were negative after proper reduction and fixation of the fracture at the time of reoperation (van den Bekerom 2011).…”
Section: Radiological Evaluationmentioning
confidence: 99%
“…However, the rotation of the limb can significantly influence each of these measurements 54 except for the TFCS on the AP view. 55 Recent studies have found great variability in the radiographic measurements of normal patients. 54,56 A study in patients without known clinical or radiographic evidence of abnormality found that the mean TFCS was 4.6 mm on the AP view and 4.3 mm on the mortise view, whereas the mean TFO was 8.3 mm on the AP view and 3.5 mm on the mortise view.…”
Section: Initial Radiographic Evaluationmentioning
confidence: 99%
“…56 Although plain weight bearing radiographs can show abnormalities, frank diastasis without fracture or applied stress is a rare occurrence. 54,55,59 External rotation stress or gravity stress views may be used to confirm latent diastasis. 13,60 Late disruption is best visualized on the lateral radiographs, with posterior displacement of the fibula.…”
Section: Initial Radiographic Evaluationmentioning
confidence: 99%
“…Unfortunately, though, there is as yet no clear consensus as to which of these tests is most valuable with respect to accurate and reliable diagnosis of occult (latent) syndesmotic instability. While it is still common practice to rely only on plain film assessment for such patients, this form of testing has the potential for demonstrated diagnostic inaccuracy due to variability in positioning and rotation of the tibiofibular joint [32]. In arguably questionable cases, similar comparative films of the opposite (presumably normal) ankle can be very helpful before more complex imaging modalities are pursued.…”
Section: Diagnosismentioning
confidence: 99%